Integration of Agriculture, Livestock, and Fisheries in Creating a Balanced and Productive Agroecosystem - Harlina, Harlina; B. Mage, Aisyah Aliyah Rahmah (Professorline, 2024)
Integrating agriculture, livestock, and fisheries is a holistic approach to natural resource management that aims to create a balanced and productive agroecosystem. This research examines the potential and challenges in integrating these three sectors, as well as their impact on environmental sustainability and economic productivity. The method used is a comprehensive literature study and analysis of secondary data from various integration projects in Indonesia. The research results show that integration of the three sectors can increase the efficiency of land, water, and nutrient use, as well as reduce waste through a closed nutrient cycle. The integrated system can also increase land productivity by up to 40% compared to conventional monoculture systems. In addition, product diversification resulting from an integrated system can increase food security and farmer income. However, implementing this system faces challenges in the form of farmers' lack of technical knowledge, limited capital, and policy obstacles. To overcome these challenges, the government needs an active role in providing technical support, access to financing, and policies that support sector integration. In conclusion, the integration of agriculture, livestock, and fisheries has great potential in realizing a balanced and productive, agroecosystem, but requires a comprehensive approach and support from various stakeholders for successful implementation.